INCIDENCE OF LAMENESS IN BROILER CHICKENS AT DIFFERENT AGE AND HOUSES - Jacob, F.G.; Baracho, M.S.; Nääs, I. A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The goal of producing broiler chicken is to reach high productivity. The objective of this study was to verify the effect of the type of house and the age of the broiler in the incidence of gait problem. The research was done using four houses named A1, A2, A3 and A4 in a commercial broiler farm during two flocks. All houses had similar dimensions, and A1, A2, and A3 had forced ventilation with positive pressure while house A4 had forced ventilation with negative pressure. The houses A1 and A4 used re-used litter, the A2 had new bedding from wood dust, and the A3 had new bedding from rice husk. Rearing environmental conditions were recorded (temperature, relative humidity, and air velocity). For evaluating the locomotor problems broilers were visually assessed, and the gait score degree was given. This evaluation used 75 broilers in each house, aging 25, 32, and 40 days. Results showed that there was an interaction of the age as a function of the rearing condition on the gait score. The effect was less intense in houses A1 and A2 than in the other studied houses. However, the effect of age was more intense in houses A3 and A4, where the gait score differed for all ages. Independent of the condition of each tested house all broilers presented lameness. The age broilers presented less lameness was at the 25 days old. Broilers from houses A3 and A4 presented higher incidence of lameness at 40 days of age.